CURRENT ISSUES IN JUVENILE JUSTICE (American Journal of Technology and Applied Sciences, 2022)
The article analyses the peculiarities of application of criminal punishment to juveniles. The need for special rules of liability in criminal law derives directly from the principles of justice and humanism. On the one hand, a child, due to his physical and mental immaturity, needs special protection and care, and therefore society cannot present him requirements equal to those imposed on persons of mature age. On the other hand, peculiarities of psychology of the juvenile allow better realization of the goals of criminal punishment by applying special, less severe punishments.